Inotropic actions of lignocaine and phenytoin - Kennedy, Barbara L. (1971)
1. The inotropic effects of two antiarrhythmic drugs, lignocaine and phenytoin, were studied in electrically driven isolated rabbit atrial preparations. The time-effect relationship of each drug was investigated with different concentrations and frequencies of stimulation. 2. The effects of time of exposure, drug concentration and heart rate on the development of beat alterations (cessation of beat, skipped beat, alternating variation of force of contraction and extrasystole) were also studied. 3. When the chronotropic effects of both drugs were prevented, the inotropic effects were positive or negative depending on the concentration of drug, time of exposure and frequency of stimulation. 4. At concentrations higher than those obtained in the blood of man on maintenance doses, alteration of the beat occurred but was consistent with the peak blood concentrations immediately after the injection of standard clinical doses. The time of onset of beat alteration shortened when either drug concentration or frequency of stimulation was increased. 5. The beat alteration produced by antiarrhythmic drugs can account for various adverse effects associated with their clinical use. These effects include transient ventricular tachycardia and extrasystole during and shortly after injection of drug, ventricular tachycardia, ventricular fibrillation and cardiac arrest due either to excessive dose or to persistent tachyarrhythmia if the dose is not excessive.